The Use of Narratives to Deliver Information in Direct-To-Consumer Prescription Drug Commercials: A Content Analysis. Issue 5 (4th May 2019) - Ball, Jennifer Gerard; Applequist, Janelle
Abstract : Information communicated through a narrative format is typically processed and evaluated differently compared to non-narrative formats. Therefore, differences in the use of narratives across various information categories within direct-to-consumer prescription drug advertisements (DTCA) could have significant implications for consumers' processing of that information. Such differences could have further implications regarding the "fair balance" rule put forth by the Food and Drug Administration (FDA). This study sought to document the presence and nature of narrative and non-narrative messages in a content analysis of 61 U.S.-based broadcast DTCA airing during 2016. Specific narrative styles (classic drama, vignette, first person, second person, third person) were distinguished from non-narrative styles (lecture, directive, endorsement, graphic/demonstration) according to key characteristics of each (chronology and character, showing versus telling). Results indicated widespread use of narrative styles in DTCA overall, but the styles used differed substantially between different types of information. Narrative styles were delivered prominently to present health condition and drug benefits information while non-narrative styles primarily reinforced drug benefits and presented drug risks. These differences offer a new frame through which to view an imbalanced presentation of drug risks and benefits and provide a foundation for future research to test the effects of various narrative and non-narrative forms on patient understanding and message recall.